Pengembangan Model Project-Based Learning Berbasis Teknologi Digital dalam Pembelajaran Bahasa Indonesia - Syihaabul Hudaa; Sarwiji Suwandi; Andayani Andayani; Kundharu Saddhono; Ahmad Bahtiar; Makyun Subuki (Balai Bahasa Sulawesi Selatan, 2025)
Challenges in education during the Industrial Revolution 4.0 era demand the optimal utilization of digital technology. However, disparities in access and low competencies of educators and learners remain major obstacles. This study aims to develop a Project-Based Learning (PjBL) model based on digital technology to improve students’ scientific writing skills in the Indonesian language course. The research method used is Research and Development (RD) with the ADDIE model, which includes needs analysis, design, development, implementation, and evaluation. Data were collected through pre-tests and post-tests of scientific writing skills, in-depth interviews, classroom observations, and student motivation questionnaires. The data were analyzed using qualitative descriptive analysis for interviews and observations, and paired t-test statistical analysis to examine the difference between pre-test and post-test scores quantitatively. The results show a significant improvement in students’ scientific writing ability, with an average pre-test score of 62.0 increasing to 79.1 in the post-test (p 0.05). Students also demonstrated high motivation and active involvement in the learning process, despite some technical challenges. This model is expected to be an effective alternative for integrating digital technology into Indonesian language learning in higher education institutions. AbstrakTantangan dalam pendidikan era Revolusi Industri 4.0 menuntut pemanfaatan teknologi digital secara optimal. Namun, disparitas akses dan rendahnya kompetensi pengajar serta pemelajar menjadi kendala utama. Penelitian ini bertujuan mengembangkan model pembelajaran Project-Based Learning (PjBL) berbasis teknologi digital untuk meningkatkan keterampilan menulis ilmiah mahasiswa pada mata kuliah Bahasa Indonesia. Metode penelitian yang digunakan adalah Research and Development (RD) dengan model ADDIE yang meliputi analisis kebutuhan, desain, pengembangan, implementasi, dan evaluasi. Teknik pengumpulan data dilakukan melalui pre-test dan post-test kemampuan menulis ilmiah, wawancara mendalam, observasi proses pembelajaran, serta kuesioner motivasi mahasiswa. Data dianalisis menggunakan analisis deskriptif kualitatif untuk data wawancara dan observasi, serta analisis statistik paired t-test untuk menguji perbedaan skor pre-test dan post-test secara kuantitatif. Hasil penelitian menunjukkan peningkatan signifikan kemampuan menulis ilmiah mahasiswa dengan rata-rata skor pre-test 62,0 menjadi 79,1 pada post-test (p 0,05). Mahasiswa juga memiliki motivasi tinggi dan keterlibatan aktif dalam pembelajaran, meskipun terdapat beberapa tantangan teknis. Model ini diharapkan dapat menjadi alternatif efektif untuk mengintegrasikan teknologi digital dalam pembelajaran Bahasa Indonesia di perguruan tinggi.